THE SITUATION OF UROLOGICAL NEPHROPATHY AMONG ADULTS AT COMMUNES, UNG HOA DISTRICT, HANOI IN 2022 (Vietnam Journal of Community Medicine, 2024)
Background: In Vietnam, research on urological nephropathy in the community is still limited, socollecting information on the status of urinary nephropathy will help us be proactive in preventingand controlling the disease.Objective: (1) Description of characteristic of adults with urological nephropathy at communes, UngHoa district, Hanoi, in 2022; (2) Description of the situation of urological nephropathy among adultsat communes, Ung Hoa district, Hanoi, in 2022Methods: Cross-sectional study. The study collected information from 589 adults who came forscreening at some communes in Ung Hoa district, Hanoi. Subjects were clinically examined, carriedout tests and interviewed by questionnaire. Data were entered by Excel and analyzed by SPSS 20.0.Results: The finding showed that the mean age of subjects (56.8 ± 14.4); in which men (59.1%),women (40.9%). Comorbidities: Hypertension (27.5%), diabetes (16.3%), cardiovascular disease(5.8%). The most common mild decrease in eGFR (63.5%). The most common prostate volume wasin the group of 20-40 ml (53.4%). The rate of urinary leukocytes (+) was 32.4%, the rate of urinarynitrite (+) was 7.1%, the rate of urinary red blood cells (+) was 15.1% and the rate of urinary glucose(+) was 4. ,6%. The rate of men with urinary stones was 8.1%, women were 18.3%, and the overallrate was 12.2%.
Keywords: Urological nephropathy, adults, communes.